Effects of Dual Task Training and Transcranial Direct Current Stimulation in Children with Spastic Cerebral Palsy: A Pilot Randomized Control Trial. - Collange-Grecco, Luanda André; Cosmo, Camila; Silva, André Luís Santos; Rizzutti, Sueli; Oliveira, Claudia Santos; muszkat, Mauro (Developmental Neurorehabilitation, 2023)
Compare the effectiveness of active and sham transcranial direct current stimulation (tDCS) during the training of a dual task in children with spastic cerebral palsy (CP). Thirty children with CP were submitted to ten sessions of either active (n = 15) or sham (n = 15) tDCS over the motor cortex for 20 minutes during the training of a dual task. Pre-intervention, post-intervention and follow-up evaluations involved measures of functional performance, intellectual performance, functional mobility and cortical excitability. The combination of active tDCS and dual task training led to improvements in functional mobility as well as functional and intellectual performances one month after the end of the intervention. The combination of active tDCS and dual task training demonstrated promising effects for children with spastic CP.